2015
DOI: 10.1038/srep10632
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of methylene blue in a novel heterogeneous Fe3O4 @rGO@TiO2-catalyzed photo-Fenton system

Abstract: Herein, a ternary nanocomposite with TiO2 nanoparticles anchored on reduced graphene oxide (rGO)-encapsulated Fe3O4 spheres (Fe3O4@rGO@TiO2) is presented as a high efficient heterogeneous catalyst for photo-Fenton degradation of recalcitrant pollutants under neutral pH. Fe3O4@rGO@TiO2 was synthesized by depositing TiO2 nanoparticles on the surface of the Fe3O4 spheres wrapped by graphene oxide (GO) which was obtained by an electrostatic layer-by-layer method. This as-prepared catalyst reflected good ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(72 citation statements)
references
References 47 publications
1
70
0
1
Order By: Relevance
“…Li and co-workers demonstrated that the singlet oxygen 1 O 2 produced from HOO· and HO· directly participates in the degradation of organic pollutants [25]. Therefore, on the basis of all the information obtained above and observations in the literatures [28][29][30], we propose that the mechanism of the H 2 (Equation (3). The generated HO 2 · can further react with ≡Fe III to produce ≡Fe II species and O 2 Equation (4), giving an explanation of those bubbles generated in the reaction process.…”
Section: Degradation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and co-workers demonstrated that the singlet oxygen 1 O 2 produced from HOO· and HO· directly participates in the degradation of organic pollutants [25]. Therefore, on the basis of all the information obtained above and observations in the literatures [28][29][30], we propose that the mechanism of the H 2 (Equation (3). The generated HO 2 · can further react with ≡Fe III to produce ≡Fe II species and O 2 Equation (4), giving an explanation of those bubbles generated in the reaction process.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) has attracted growing research interests in various fields, such as Li ion batteries [1], catalysts [2], drug delivery and targeting [3], etc., due to its distinguished physical and chemical properties [4,5]. However, these magnetite Fe 3 O 4 nanoparticles (MNPs) may aggregate into large clusters because of the anisotropic dipolar interactions, reducing their dispersibility and other specific properties and ultimately diminishing their activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene and graphene based 38 materials is getting special interest as template for different 39 nanoparticles due to their high surface area, and possibility of 40 electrostatic interaction with the nanoparticles [8][9][10][11]. Graphene 41 oxide shows amphiphilic nature due to the presence of oxygen 42 containing functional groups like carboxyl, hydroxyl and epoxide 43 groups at the edges and hydrophobic unoxidized polyaromatic 44 islands within the basal plane and therefore it can be effectively 45 used as template/precursor for the growth of different kinds of 46 nanoparticles [8][9][10][11]. In this study, graphene oxide used as 47 precursor of the template for the growth of the Fe 3 O 4 nano- 48 particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, TiO 2 has a large band gap (3.2 eV for anatase and 3.0 eV for rutile) and can only respond to ultraviolet (UV) irradiation, which restrict its practical application [20][21][22][23]. Moreover, a number of intermediates are usually produced during the TiO 2 photocatalytic degradation process, and are difficult to be further degraded.…”
Section: Introductionmentioning
confidence: 99%